İstanbul semtleri̇ özeli̇nde mevki̇li̇ tramvay yolculuğunun değerlendi̇ri̇lmesi̇ (1920-1930) - ARISAL, MURAT (My University, 2022)
Tramvayın modern bir ulaşım aracı olarak İstanbul halkının hayatına girmesi, kimi davranış kalıplarının değişimini de beraberinde getirmiştir. Osmanlı başkentinde yan yana zengin fakir aynı mahallelerde birlikte yaşayan ahali, mevkili tramvay kullanımıyla ekonomik durumlarına göre sınıflandırıldıkları yeni bir tüketim davranışıyla karşı karşıya kalmıştır. Daha fazla para ödeyerek birinci mevkide seyahat etmenin sağladığı ayrıcalık, toplum kesimlerinin ekonomi temelli ayrışmasında öncü rol oynamıştır. Mevkilerine göre seyahatin dağılımının analizi ve semtler arası farklılıkların karşılaştırılması, dönemin toplum yapısı ve ekonomik durumu hakkında çok değerli veriler sunmaktadır. Birinci ve ikinci mevki tramvay araçlarının, İstanbul toplu ulaşımının ana omurgasını teşkil ettiği 1920-1930 yıları arasına ait Tramvay Şirketi’nin performansı, yolcuların mevkilerine göre farklılaşan konforlarının sınırlarını belirlemektedir. Çalışma dönemi boyunca ana güzergâhları oluşturan tramvay hatlarının her birinin grafikleri kendi özelinde değerlendirilerek, analizleri karşılaştırmalı olarak yapılmıştır. Açılan ve kapanan tramvay hatları, birinci mevki araçların ısrarla kaldırılmasının istendiği güzergâhlar, birinci mevki araçların kullanımının tercihen mi yoksa bir tür zorunluluktan mı kaynaklandığı belgeler ve veriler ışığında irdelenmiştir.

The introducion of the tram into the lives of the people of İstanbul as a modern form of transportation has generated a change in some behavioral patterns. The use of local trams have caused the people living together in the same neighborhoods, rich and poor, side by side in the Ottoman Capital to be faced with a new consumption behavior in which they were classified according to their economic status. The privilege of traveling in first class by paying more has played an important role in the economic based separation of parts of society. The analysis of the distribution of tram travels according to the passengers classes and the comparison of the differences between the districts provided substantial data about the social structure and economic conditions of the period. Between the years of 1920-1930, when first and second class trams were formed the backbone of public transportation in İstanbul, the performance of the Tram Company was determined by the comfort standards of passengers which were differed according to their classes. The trams which constituted the main routes of İstanbul throughout their working period, were evaluated separately and were analyzed comperatively. The issues such as the tram lines that were repeatedly opened and closed, the routes where the first class vehicles were insistently removed and the question of whether the use of first class vehicles were used by preference or by necessity have been examined in the light of documents and data.
Evaluation of The Local Tramway Travel Within İstanbul Neighborhoods (1920-1930)
Keywords: Medieval Europe; Burgundy; Travel Writing; Sultan Mehmed II; Sultan Bayezid II; Cem Sultan; Birinci mevki; ikinci mevki; tramvay; ulaşım; İstanbul semtleri